Impact of high-power and very high-power short-duration radiofrequency ablation on procedure characteristics and first-pass isolation during pulmonary vein isolation. (19th May 2022) - Sallo, Z; Perge, P; Piros, K; Herczeg, SZ; Nagy, KV; Osztheimer, I; Abraham, P; Merkely, B; Geller, L; Szegedi, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: High-power short-duration (HPSD) radiofrequency ablation has been proposed as a method for producing rapid and effective lesions for pulmonary vein isolation.We aimed to evaluate the procedural characteristics and the FPI rate of HPSD and very high-power short-duration (vHPSD) compared to low-power long-duration (LPLD) ablation techniques. Methods: 156 patients with atrial fibrillation (AF) were enrolled and assigned to LPLD, HPSD, or vHPSD PVI. The energy setting was 30W, 50W, and 90W in the LPLD, HPSD, and vHPSD groups, respectively. Results: Bilateral PVI was achieved in all cases. The procedure time was 85 [75-101] min, 79 [65-91] min, and 70 [53-83] min in the LPLD, HPSD, and vHPSD groups, respectively (p<0, 0001). LA dwelling times were also decreased significantly with the increase of RF energy (61 [55-70] min, 53 [41-56] min, and 45 [34-52] min, in the LPLD, HPSD, and vHPSD groups, respectively, p<0.0001). The total RF ablation time was 1398 [1021-1711] sec, 1567 (1366-1761) sec, and 336 [247-386] sec in the LPLP, HPSD, and vHPSD group, respectively ( p<0, 0001). Bilateral FPI was rate was 57%, 78% and 80% in the LPLD, HPSD, and vHPSD groups, respectively (p=0, 0097). On the left side, FPI was achieved in 66% in the LPLD, in 92% in the HPSD, and in 85% in the vHPSD ablation group (p=0.0015). FPI on the right side was achieved in 72% in the LPLD, in 88% in the HPSD, and in 88% in the vHPSD ablation group (p=0, 0188). FPI rates were significantly higher in the HPSD group compared to the LPLD group: both sided FPI rate was 57% vs. 78% (p=0.021), left sided FPI rate was 66% vs. 92% (p=0.0015), and right sided FPI rate was 72% vs. 88% (p=0.0401). Further increase in the RF power did not result in a significant additional increase in the FPI rate. In the HPSD vs. vHPSD group both sided FPI rate was 78% vs. 80% (p=0, 8080), left sided FPI rate was 92% vs. 85% (p= 0, 5275), and right sided FPI rate was 88% vs. 88% (p= 0, 7561). Univariate analysis revealed that the use of HPSD ablation technique is associated with a higher probability of FPI (both sides: OR=2.72, 95% CI 1.15-6.44, p=0.023; right side: OR=2.90, 95% CI 1.02-8.20, p=0.045; left side: OR=5.91, 95% CI 1.84-19.04, p=0.003). The mid-term arrhythmia-free survival was similarly high in all three groups. Conclusion: Our prospective, observational cohort study showed that both HPSD and vHPSD RF ablation is effective, as it shortens procedure time and RF time and results in a higher rate of FPI compared to LPLD ablation. Moreover, the mid-term arrhythmia-free survival was similarly high in all three groups. In our study, no safety concerns were raised due to HPSD ablation.